Existence and Uniqueness of Mild Solution for Mixed type of Integro-Differential Equation - Akram H. Mahmood; Sara F. Abdullah (College of Education for Pure Sciences, 2018)
In this paper, we study the existence and uniqueness of a mild solution of a nonlinear mixed Volterra - Fredholm integro-differential equation with nonlocal condition in Banach space. Furthermore, we study continuouce dependence of mild solution. Our analysis is based on semigroup theory and Banach fixed point theorem.